Biventricular diastolic dysfunction, thrombocytopenia, and red blood cell macrocytosis in experimental pulmonary arterial hypertension. (May 2020) - Lee, Ji Young; Fagan, Karen A.; Zhou, Chun; Batten, Lynn; Cohen, Michael V.; Stevens, Troy
Pulmonary arterial hypertension is a fatal disease, where death is associated with right heart failure and reduced cardiorespiratory reserve. The Sugen 5416, hypoxia and normoxia Fischer rat model mimics human pulmonary arterial hypertension, although the cause(s) of death remains incompletely understood. Here, we hypothesized that these animals develop biventricular diastolic dysfunction that contributes to tissue hypoperfusion coincident with severe pulmonary arterial hypertension. We performed comprehensive echocardiographic and hematologic assessments. Serial echocardiogram at 3–5 weeks was performed followed by blood sampling via aortic or cardiac puncture. Echocardiogram revealed pulmonary arterial hypertension in pulmonary artery Doppler waves, including notched wave envelopes, and decreased pulmonary artery acceleration time/pulmonary artery ejection time ratio and right ventricular outflow tract velocity time integral. Impaired right ventricular systolic function, assessed by decreased tricuspid annular plane systolic excursion and tricuspid tissue Doppler systolic positive wave velocity, was observed in pulmonary arterial hypertension. Tricuspid and mitral pulsed wave and tissue Doppler findings suggested biventricular diastolic dysfunction, with dynamic changes in early and late diastolic filling waves, their fusion patterns, and a decrease in e' velocity. Heart rate and ejection fraction did not change, but cardiac output, stroke volume, and end-diastolic volume were decreased, and inferior vena cava respiratory variation was decreased. Blood electrolyte values were suggestive of intravascular volume expansion early in the disease followed by volume contraction and tissue hypoperfusion in the latter stages of disease. Complete blood count showed thrombocytopenia and non-anemic macrocytosis with reticulocytosis and an increase in red blood cell distribution width. Thus, pulmonary, cardiac, and hematological findings in Fischer animals with pulmonary arterial hypertension are characteristic of humans and provide an insightful experimental platform to resolve mechanisms of disease progression.